The Methods of Factor Weight’s Determine in the Process of Cluster - Wang Dinglei; Li Jianyong; Xu Wensheng (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
The goal of product design is to meet the anticipated design goal. The process of product’s modularization should accommodate the multi-design objective. The rules and the its factor weight are determined impersonally by the method of AHP (Analytic Hierarchy Process) for the different goal. There are various relationships between the parts, such as continuity, noncontinuity, and simply relationship. The different calculated methods are studied base on the different character between the parts’ interaction values, and the objectivity and accuracy have been improved. DOI: http://dx.doi.org/10.11591/telkomnika.v10i5.1344